Membangun Consumer Loyalty melalui Social Media - MARLIYA, NOVA MEI; WAHYONO, WAHYONO (Management Analysis Journal, 2016)
This study aims to knowing the marketing strategies applied to the company through social media and promotions that can influence and build consumer loyalty. The population in this study is all Zalora consumer. The number of samples is 110 respondents. The sampling technique is Purposive Sampling. The data collection is using the questionnaire/question form. The method of data analysis is using SEM analysis (Structural Equation Modelling) with tool analysis is IBM SPSS AMOS 21 program. The results of the study shows that the research design using variable social media, product position, promotion, purchase decision, satisfaction, and loyalty that these models generally well/fit accepted by the result of calculation of index values that meet the criteria for goodness of fit index. The hypothesis presented in this study are 10 hypothesis with 5 hypothesis result has a significant influence (p<0.05) and 5 other hypothesis has a not influence with significant value (p>0.05). The conclusion of this study proves that the higher implementation of social media, it can improve on consumer loyalty, while promotion of the applied can’t influence on consumer loyalty.